Public Perceptions of Per- and Polyfluoroalkyl Substances (PFAS): Psycho-Demographic Characteristics Differentiating PFAS Knowledge and Concern - Kemper, Joya; Sharp, Emma; Yi, Shan; Leitao, Erin; Padhye, Lokesh; Kah, Melanie; Chen, Jack L-Y; Gobindlal, Kapish (Elsevier BV, 2024)
Due to their persistence and toxicity, per- and polyfluoroalkyl substances (PFAS) have become an issue of global concern. The public's perception is valuable in consultations about possible remediation of or mitigation against the use of PFAS. In this study, we investigated the source of PFAS information and factors (psycho-demographic characteristics) affecting public views. We performed an online survey with a demographically representative sample of Aotearoa New Zealand adults (n = 935). Results show that PFAS are known to nearly 45 % of the survey participants, yet, with misunderstandings. Amongst those aware of PFAS, the concern is high, especially for their use in products that contact skin or consumed orally. Individuals with the highest level of self-perceived PFAS knowledge (vs no knowledge) were most concerned but also the most accepting of PFAS-containing products. Males were self-perceived to be more knowledgeable and less concerned than females. Younger adults (aged 18–34) were more likely to indicate high perceived knowledge and more acceptance of consumer products containing PFAS than older adults. These findings identified crucial information gaps that will contribute to national and global regulation and policy decisions as well as inform public education campaigns, informing a more targeted education approach.
Keywords: 40 Engineering; 33 Built Environment and Design; Clinical Research; 4 Quality Education; 0907 Environmental Engineering; 0910 Manufacturing Engineering; 0915 Interdisciplinary Engineering; Environmental Sciences; 33 Built environment and design; 40 Engineering